Solve for y 3*(-4y)=16

Math
3⋅(-4y)=16
Multiply -4 by 3.
-12⋅y=16
Divide each term by -12 and simplify.
Tap for more steps…
Divide each term in -12⋅y=16 by -12.
-12⋅y-12=16-12
Cancel the common factor of -12.
Tap for more steps…
Cancel the common factor.
-12⋅y-12=16-12
Divide y by 1.
y=16-12
y=16-12
Simplify 16-12.
Tap for more steps…
Cancel the common factor of 16 and -12.
Tap for more steps…
Factor 4 out of 16.
y=4(4)-12
Cancel the common factors.
Tap for more steps…
Factor 4 out of -12.
y=4⋅44⋅-3
Cancel the common factor.
y=4⋅44⋅-3
Rewrite the expression.
y=4-3
y=4-3
y=4-3
Move the negative in front of the fraction.
y=-43
y=-43
y=-43
The result can be shown in multiple forms.
Exact Form:
y=-43
Decimal Form:
y=-1.3‾
Mixed Number Form:
y=-113
Solve for y 3*(-4y)=16

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top